Primary cutaneous neuroendocrine carcinoma with diffuse expression of thyroid transcription factor-1: Report of two cases - Jose Maria Ortiz Salvador; Daniela Subiabre-Ferrer; Victor Alegre de Miquel (Wolters Kluwer Medknow Publications, 2019)
Primary cutaneous neuroendocrine carcinoma (PCNC), previously known as Merkel cell carcinoma (MCC), is a rare tumor of the skin with aggressive behavior and poor prognosis. Typically, PCNC is positive for Cytokeratin-20 (CK20) and negative for Thyroid Transcription Factor-1 (TTF-1). Rarely, CK-20 negative and TTF-1 positive PCNC have been described. We present the case of two patients with skin lesions histologically compatible with MCCs and a behavior characteristic of this disease, but with expression of TTF-1 instead of CK-20. In conclusion, there are increasing reports of TTF1+ CK20− skin lesions without signs of systemic disease which behave clinically and prognostically like a PCNC. The origin of these TTF1 tumors are, to date, unknown.